Mapping the Intertidal Microphytobenthos Gross Primary Production Part I: Coupling Multispectral Remote Sensing and Physical Modeling - Méléder, Vona; Savelli, Raphael; Barnett, Alexandre; Polsenaere, Pierre; Gernez, Pierre; Cugier, Philippe; Lerouxel, Astrid; Le Bris, Anthony; Dupuy, Christine; Le Fouest, Vincent; Lavaud, Johann (Frontiers in Marine Science, 2020)
The Gross Primary Production (GPP) of intertidal mudflat microphytobenthos supports important ecosystem services such as shoreline stabilization, food production and it contributes to the Blue Carbon. However, monitoring microphytobenthos GPP over long term and large spatial scale is rendered difficult by its high temporal and spatial variability. To overcome this issue, we developed an algorithm to map microphytobenthos GPP in which are coupled: (i) NDVI maps derived from high spatial resolution satellite images (SPOT6 or Pléiades) estimating the horizontal distribution of the microphytobenthos biomass; (ii) emersion time, photosynthetically active radiation (PAR), and mud surface temperature simulated from the physical model MARS-3D; (iii) photophysiological parameters retrieved from Production-Irradiance (P-E) curves obtained under controlled conditions of PAR and temperature using benthic chambers and expressing the production rate into mg C h-1 m-2 ndvi-1. The productivity was directly calibrated to NDVI to be consistent with remote-sensing measurements of microphytobenthos biomass, and spatially upscaled using satellite-derived NDVI maps acquired at different seasons. The remotely-sensed microphytobenthos GPP reasonably compared with in situ GPP measurements. It was highest in March with a daily production reaching 50.2 mg C m-2 d-1, and lowest in July with a daily production of 22.3 mg C m-2 d-1. Our remote sensing algorithm is a new step in the perspective of mapping microphytobenthos GPP over large mudflats to estimate its actual contribution to ecosystem functions, including blue carbon, from local and global scales.